Financial structure gap and economic development in India - Sethi, Pradeepta; Kumar, Brajesh (Journal of Business Economics and Management, 2014)
This study is built on the concept of optimal financial structure and examines its dynamics with the economic development process of India. Specifically, the present study intends to examine the evolving importance of banks and markets during different stages of economic development. Using annual data from 1988–2009 for India and selected benchmark OECD countries, we have conducted quantile and robust regression to assess the impact of deviation from the optimal financial structure on the output growth. To our knowledge the present study is one of the pioneer works in calculating the optimal financial structure in Indian context. The empirical evidence suggests that as the economy develops the services provided by banks are comparatively more important than those provided by the stock markets. The financial structure matters for the growth process. The deviation from the optimal structure has harmful effects on the economy and the financial structure gap retards the growth process. First published online: 16 Jan 2013